Michel Foucault, Lust, Women, and Sin in Louis XIV's Paris - Riley, Philip F. (Church history, 1990)
Since 1984, the year of his death, a veritable cottage industry of criticism has appeared to decipher, decode, and demolish Michel Foucault. Despite the polemics, ambiguities, and, at times, the impenetrability of his prose, Foucault and his critics do agree that one of the central concerns of his work, particularly his early work, was an analysis of power and how such institutions as police, prisons, and churches reflect the power structures of society.